Dyslipidemia and cardiovascular changes in children. (January 2016) - Pires, António; Sena, Cristina; Seiça, Raquel
Abstract : Purpose of review: In this review, we firstly highlight the role of dyslipidemia as a trigger in the initiation and progression of endothelial dysfunction, considered the earliest atherosclerotic lesion and patent in children with risk factors. In this context, we also revise methods that reflect the impact of endothelial dysfunction not only on arterial stiffness but also on cardiovascular morphology, namely, the common carotid intima-media thickness and the ventricular geometry. Recent findings: In view of its atherogenic burden, the most widely studied lipoprotein has been low density lipoprotein cholesterol. However, the smaller, denser, low density lipoprotein cholesterol particles, the nonhigh density lipoprotein cholesterol fraction, appear to be more atherogenic and a more sensitive cardiovascular risk marker. Studies have shown that in children, atherogenic lipids have also been linked to cardiovascular morphological changes, such as the common carotid intima-media thickness and the ventricular geometry, both independent cardiovascular risk markers. Summary: In infancy, atherosclerosis is a preclinical disorder in which dyslipidemia plays a crucial role. Due to its impact on cardiovascular structures, potentially reversible during childhood, dyslipidemia ought to be managed aggressively to prevent further disease progression that will ultimately culminate in cardiac disease, a leading cause of mortality in adults.